THE DEVELOPMENT OF STRATEGY IN SPORTS MANAGEMENT FOR EXCELLENCE OF THAILAND NATIONAL SPORTS UNIVERSITY - Huahin, Suriyan; Mahakeeta, Ann (Journal of MCU Nakhondhat, 2026)
This research aimed to study general information regarding sports management strategies for excellence and to develop and validate the appropriateness and feasibility of sports management strategies for excellence at the National Sports University. This study utilized a Research and Development (R&D) design divided into three distinct phases. Phase 1 involved studying fundamental data from 10 experts and 264 stakeholders using semi-structured interviews and questionnaires. Data were analyzed using mean, standard deviation, and the PNI Modified index. Phase 2 focused on drafting the strategies, which were reviewed by 19 experts. Phase 3 involved confirming the final strategies with 284 stakeholders by calculating median and interquartile range values. The research results revealed that the development of sports for excellence consists of nine key components: finance, organization and structure, sports participation, system development and talent identification, professional sports, facilities and equipment, recruitment and coach development, national and international competition management, and innovation and research. Upon ranking these components, it was found that the highest priority need was finance, followed by professional sports careers and sports participation, respectively. The strategic development for sports management for excellence at the National Sports University includes a vision: "The National Sports University is a leading university in sports for excellence at both national and international levels." This framework further comprises six missions, seven goals, six strategies, and six core tactics. When evaluating and confirming the feasibility of these sports management strategies for excellence at the National Sports University, the results indicated that the vision, missions, goals, strategies, and tactics were all at a high level across every dimension. These findings provide a comprehensive framework for elevating the university's competitive standards and ensuring sustainable athletic success through systematic management and strategic resource allocation aligned with international standards.